Minimum fluidization velocities of binary and ternary biomass mixtures with silica sand. (November 2020) - Soanuch, Chaiwat; Korkerd, Krittin; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: Minimum fluidization velocity is an important property which can influence the hydrodynamics and chemical conversion in fluidized bed reactor. Most of the fluidized bed boilers usually mix raw biomass solid particles with medium silica sand solid particles. This is because the biomass supply is varied with the season and location. The objective of this study is to investigate the effect of binary and ternary biomass mixtures with medium solid particles on the obtained minimum fluidization velocity. The experiment was conducted with three types of biomass including, wood chip, rice husk and palm shell waste, together with silica sand. The biomass mixtures were mixed according to the mixture experimental design. The results showed that the mixture of biomass could improve the hydrodynamics inside the system. The minimum fluidization velocity was thus decreased when conducting the experiment with the binary and ternary biomass-silica sand mixtures. The obtained minimum fluidization velocity range was 0.19 to 0.37 m/s.